Northerly and Southerly Wind Events in the Eastern Bay of Campeche, Mexico - Geimond Jarumi Antemate‐Velasco; Gabriela Athié; Mark Marín‐Hernández; Ruth Cerezo‐Mota; Jorge A. Kurczyn; Alejandro Granados‐Barba (International Journal of Climatology, 2025)
Cold surges entering the Gulf of Mexico (GoM) generate northerly winds (Norte events), preceded by warm southerly winds (Surada events). These events were characterised in the Eastern Bay of Campeche (EBC) using ERA5 reanalysis data for 2002–2024. Both Norte and Surada events exhibited distinct intensity and predominant direction patterns in the EBC, compared with the broader GoM. Therefore, the separate identification of both events specific to the EBC was proposed. A minimum wind magnitude threshold (E) was determined for the EBC, above which events were considered sufficiently intense to be classified as Norte (2.4 ms −1 ) or Surada (1.3 ms −1 ) events in this region. It was shown that Norte events lasting −1 . Empirical Orthogonal Functions analysis for the southern GoM revealed that, in ~30% of the cases (Modes 2 and 3), cold fronts moved with a significant zonal component in the southern GoM. This pattern was associated with intense Surada events and weak or even absent Norte events in the EBC. Mode 1 accounted for more than 63% of the variability and corresponded to Surada events followed by Norte events with similar behaviour in the entire region. This study demonstrates a distinct wind behaviour associated with cold surges on the eastern and western sides of the Bay of Campeche in the southern GoM. Norte and Surada events can negatively impact local marine and fisheries sectors, as wind intensity forecasts are often generalised for the entire GoM and can be unreliable in the EBC. These events are critical for coastal circulation and influence ecosystem dynamics, fisheries, and key oceanographic processes such as coastal‐trapped waves, upwellings, and wave fields.